2020
DOI: 10.3390/ijms21124258
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Compounds and MAPK Signaling Pathways

Abstract: The molecular signaling pathways that lead to cell survival/death after exposure to organophosphate compounds (OPCs) are not yet fully understood. Mitogen-activated protein kinases (MAPKs) including the extracellular signal-regulated protein kinase (ERK), the c-Jun NH2-terminal kinase (JNK), and the p38-MAPK play the leading roles in the transmission of extracellular signals into the cell nucleus, leading to cell differentiation, cell growth, and apoptosis. Moreover, exposure to OPCs induces ERK, JNK, and p38-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Several studies (31)(32)(33) have reported that JNK translocates to the nucleus after its activation and is involved in cellular functions via the phosphorylation of transcription factors in the nucleus. However, some studies (11,(34)(35)(36) have suggested that JNK not only serves a role in the nucleus, but also in the localization and regulation in other parts of the cells by binding to a specific protein, such as Sab (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (31)(32)(33) have reported that JNK translocates to the nucleus after its activation and is involved in cellular functions via the phosphorylation of transcription factors in the nucleus. However, some studies (11,(34)(35)(36) have suggested that JNK not only serves a role in the nucleus, but also in the localization and regulation in other parts of the cells by binding to a specific protein, such as Sab (11).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway is commonly stimulated by a plethora of stress conditions and inflammatory cytokines, resulting in a cascade of phosphorylation and other signaling events that initiate changes for the appropriate biological response (cellular adaptation for survival or death) [ 53 , 54 ]. Many members of the MAPK family of proteins are implicated in a number of neuroinflammatory diseases [ 55 , 56 ], and previous research has shown that the MAPK signaling pathway is activated by AChEIs [ 56 , 57 ], which drives the neuroinflammatory effects of AChEI exposure. Two of the main families of MAPKs were measured in this study: extracellular signal-regulated kinases (ERKs) and c-Jun N-terminal kinases (JNKs).…”
Section: Discussionmentioning
confidence: 99%
“…Since the metabolism of astrocytes is an in dissociable link between neuronal health and synaptic functions, it is important to be mindful of how environmental toxicants can impact human health. Furthermore, environmental toxicant exposure can result in glucose dysfunction, including the involvement of the GLUT1 transporter, especially the astrocyte-specific transporter [13] . Within the CNS, there is an overlap between the peripheral and astrocytic mechanisms.…”
Section: Discussionmentioning
confidence: 99%